The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/jog.14132
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype and genotype of polycystic ovary syndrome in Asia: Ethnic differences

Abstract: Polycystic ovary syndrome (PCOS) is a common endocrine disorder in reproductive-aged women, and ethnic diversity has been reported in its manifestation. This review addressed phenotype and genetic studies in Asian women with PCOS. Generally, East Asians are less hirsute, and the hirsutism score cutoff is lower than the Caucasian counterpart. It is not clear whether there are any significant differences in the prevalence or severity of irregular menstruation (IM) or characteristics of polycystic ovary (PCO) acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 80 publications
1
36
0
Order By: Relevance
“…8 Polycystic ovary syndrome (PCOS) is a common endocrine disorder in women of reproductive age and irregular menstruation, and the polycystic ovary subgroup is relatively common in Asian ethnicities. 10 In addition, genetic studies on PCOS reported that there is polymorphism in follicular stimulating hormone receptor gene, which plays key role in a menstrual cycle. 11,12 These might be the reasons for the higher risk of irregular menstrual cycles in Asian ethnicities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Polycystic ovary syndrome (PCOS) is a common endocrine disorder in women of reproductive age and irregular menstruation, and the polycystic ovary subgroup is relatively common in Asian ethnicities. 10 In addition, genetic studies on PCOS reported that there is polymorphism in follicular stimulating hormone receptor gene, which plays key role in a menstrual cycle. 11,12 These might be the reasons for the higher risk of irregular menstrual cycles in Asian ethnicities.…”
Section: Introductionmentioning
confidence: 99%
“…The Nurse's Health Study II showed that women of Asian ethnicity had a higher risk of irregular menstrual cycles than that of white people (PR: 1.38, 95% confidence interval [CI]: 1.19‐1.61) 8 . Polycystic ovary syndrome (PCOS) is a common endocrine disorder in women of reproductive age and irregular menstruation, and the polycystic ovary subgroup is relatively common in Asian ethnicities 10 . In addition, genetic studies on PCOS reported that there is polymorphism in follicular stimulating hormone receptor gene, which plays key role in a menstrual cycle 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite confounding factors that could not be excluded from the study, such findings may indicate that different genetic components could play different extends of roles in the disease development, leading to different manifestations. For instance, it was reported that East Asian patients with PCOS were more likely to have diabetes compared with Caucasian patients [56]. Thus, continuous genome-based studies are needed to personalize the diagnosis and management of PCOS across different ethnicities.…”
Section: Discussionmentioning
confidence: 99%
“…Recent meta-systemic analyses pointed out at large trials variation (5-13%) in the overall prevalence of PCOS, according to the National Institutes of Health, Rotterdam and Androgen Excess Society criteria. [1][2][3] These variations are due to problematic definitions of the PCOS syndrome and its phenotypic expression (e.g. hyperandrogenism to hirsutism, anovulation to infertility, amenorrhea to irregular/heavy uterine bleeding, insulin resistance to obesity), as well as its diagnostic cut-off between different study size cohorts and ethnicities in an unselected population, and these criteria contribute in patients' PCOS diagnosis bias.…”
Section: Introductionmentioning
confidence: 99%
“…hyperandrogenism to hirsutism, anovulation to infertility, amenorrhea to irregular/heavy uterine bleeding, insulin resistance to obesity), as well as its diagnostic cut-off between different study size cohorts and ethnicities in an unselected population, and these criteria contribute in patients' PCOS diagnosis bias. [1][2][3][4] Hence, identifying the correct PCOS etiology is pivotal in adopting the best clinical practices.…”
Section: Introductionmentioning
confidence: 99%